Gildas's De Excidio Britonum and the Early British Church. By Karen George - Woods, David (The journal of theological studies, 2009)
This is a revised version of the doctoral dissertation which Karen George completed under the supervision of Professor I. N. Wood of the School of History at the University of Leeds in 2005. The British author Gildas composed the De Excidio Britonum (henceforth DEB) c.540, and this is the first monograph devoted to this perplexing text since that by T. D. O'Sullivan in 1978, and the first major publication on it since the important collection of essays edited by M. Lapidge and D. N. Dumville in 1984. George does not set out to prove one major thesis, nor does she restrict herself to a single approach or methodology.